Abluminal biodegradable polymer biolimus-eluting versus durable polymer everolimus-eluting stent in patients with diabetes mellitus: 5 years follow-up from the COMPARE II trial. (1st September 2019) - Paradies, Valeria; Vlachojannis, Georgios J.; Royaards, Kees-Jan; Wassing, Jochem; van der Ent, Martin; Smits, Pieter C.
Abstract: Background: Drug eluting stents with biodegradable polymers have been developed to address the risk of very late adverse events. Long-term comparison data between the biodegradable polymer-coated biolimus-eluting stent (BES; Nobori®) and the second-generation durable polymer-coated everolimus-eluting stent (EES; XIENCE V® or XIENCE PRIME® or PROMUS™) in diabetic patients are scarce. Methods: The COMPARE II trial was an investigator-initiated, multicenter, open-label, randomized, all-comers trial which assigned patients undergoing percutaneous coronary intervention (PCI) in a 2:1 fashion to either BES or EES. We analyzed the safety and efficacy outcomes in diabetic patients at 5 year follow-up. The primary pre-specified composite endpoint major adverse cardiac event (MACE) was defined as cardiac death, non-fatal target-vessel myocardial infarction (TV-MI), or clinically indicated target vessel revascularization (CD-TVR). Results: Out of 2707 study patients, 588 were diabetics (21.7%) of whom 391 were treated with BES and 197 with EES. At 5 years follow-up, MACE occurred in 87 patients (22.2%) in the BES group and in 34 patients (17.2%) in the EES group ( p  = .34). Other safety and efficacy endpoints did not differ between stent groups. Conclusions: At 5 years follow-up, no differences in terms of MACE as well as all analyzed safety and efficacy measures, including stent thrombosis, between the biodegradable polymer-coated BES and the durable polymer-coated EES in diabetic patients were observed. Highlights: DM continues to negatively impact on the performance of new-generation DES. Higher rates of adverse events are reported in diabetic patients. No difference in terms of MACE and TLF were detected between BES and EES groups.